2020
DOI: 10.1016/j.jclepro.2020.122111
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency assessment of rural domestic sewage treatment facilities by a slacked-based DEA model

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…However, Frick et al [26] and Bartiaux [27] found no correlation between environmental knowledge and behavior. Recently, the issues of solid waste discharge [28][29][30], domestic sewage discharge [31][32][33][34][35], and rural household toilet reform [36][37][38] have received much attention. Farmers' participation in agroecological production [39][40][41][42], agricultural land rehabilitation [43,44], and environmental management [45][46][47][48] has been discussed, and it provides a useful reference for this paper.…”
Section: Introductionmentioning
confidence: 99%
“…However, Frick et al [26] and Bartiaux [27] found no correlation between environmental knowledge and behavior. Recently, the issues of solid waste discharge [28][29][30], domestic sewage discharge [31][32][33][34][35], and rural household toilet reform [36][37][38] have received much attention. Farmers' participation in agroecological production [39][40][41][42], agricultural land rehabilitation [43,44], and environmental management [45][46][47][48] has been discussed, and it provides a useful reference for this paper.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to providing overall efficiency scores, software MaxDEA can also provide target improvement for each DUM, including all inputs and outputs (Cheng et al 2020). In other words, taking efficient samples as benchmark, it can quantify potential improvement of each item for inefficient DMUs to improve scores of inefficient enterprises.…”
Section: Inputs and Outputsmentioning
confidence: 99%
“…Conventional DEA methods, which are also called radial models, have focused on the input and output changes proportionally. On the other hand, the non-radial slacks-based measure DEA approach takes into consideration target improvement ratios (IR) for each inefficient unit (Cheng et al, 2020). Besides, the slack-based DEA is an advantageous technique as it can optimize desired and undesired output concurrently (Sun and Huang, 2021).…”
Section: Introductionmentioning
confidence: 99%